2006
DOI: 10.2174/187153006778250019
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumor-Related Immunosuppression for Cancer Immunotherapy

Abstract: Tumors produce several factors, such as Prostaglandins (PGs), Interleukin (IL)-10, Vascular Endothelial Growth Factor (VEGF) and Transforming Growth Factor (TGF)-beta, which may directly or indirectly inhibit the immune response and may hamper immunotherapy. Furthermore, cells of innate or adaptive immunity, recruited by tumor-derived factors, may contribute in immunosuppression. Regulatory T (Treg) cells such as the "naturally occurring" CD4(+)/CD25(+) Treg and the IL-10-induced Tr1 cells are major players in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 165 publications
(221 reference statements)
1
62
0
1
Order By: Relevance
“…TCR ligation without costimulation can induce T cell anergy (2) or T cell apoptosis (3). In several in vivo pathologic settings, such as chronic infections or with a progressively growing tumor, the development of T cell dysfunction has been observed (4). Several lines of investigation have suggested that this dysfunction is mediated through immune-intrinsic negative regulatory pathways (5).…”
Section: Introductionmentioning
confidence: 99%
“…TCR ligation without costimulation can induce T cell anergy (2) or T cell apoptosis (3). In several in vivo pathologic settings, such as chronic infections or with a progressively growing tumor, the development of T cell dysfunction has been observed (4). Several lines of investigation have suggested that this dysfunction is mediated through immune-intrinsic negative regulatory pathways (5).…”
Section: Introductionmentioning
confidence: 99%
“…However therapeutic immunization with the pDNA vaccine could not eradicate established tumor completely. One possibility is that the growing B16F10 tumor secretes immunosuppressive cytokines such as VEGF, IL-10 and TGF-ß which prevent the activated CTLs from entering into the tumor (23,24). Here we find that the efficacy of vaccination can be substantially enhanced by blocking angiogenesis in tumor.…”
Section: Discussionmentioning
confidence: 63%
“…Once the immune system of the host was dysfunctional, tumors escaped the immune surveillance to transform cancers (23). Furthermore, tumor cells released some immunosuppressive cytokines, such as prostaglandins, vascular endothelial growth factor and transforming growth factor-beta to directly or indirectly inhibit the immune response (24). In the GSEA results, the researchers surprisingly found that 12 pathways related to the immune system were significantly down-regulated, which indicated that the immune system was strongly altered/inhibited in NSCLC (25).…”
Section: Discussionmentioning
confidence: 99%